Local Culture as a Carriage of Social Solidarity Value - Warto Warto (Jurnal Penelitian Kesejahteraan Sosial, 2014)
This study means to reveal the form, meaning, and Javanese cultural influence on local culture as social solidarity value carriage in rural community in preserving social solidarity. The approach used in this study is qualitative, revealing subjective meaning deeply of social phenomenon in their local living place. This study is implemented two local cultural tourism settings, Kebonagung Village, Imogiri Underdistrict, Bantul Regency. Data resources determined purposively, are they who know comprehensively on local culture and able to inform clearly on cultural components as community carriage to preserve social solidarity value. Data are gathered through interview, field observation, and documentary analysis. The result shows that in effort to preserve social solidarity, local community in those two villages always use local culture that manifested through tradition, expression, and local art. It is recommended that the government, through the Ministry of Social Affairs via the Directory of Heroism, Pioneering, and Social Solidarity make a policy model on social solidarity preservation, and the program activities that published is made in harmony with local culture existence.